2014
DOI: 10.1002/ajmg.a.36780
|View full text |Cite
|
Sign up to set email alerts
|

Major congenital anomalies in babies born with Down syndrome: A EUROCAT population‐based registry study

Abstract: Previous studies have shown that over 40% of babies with Down syndrome have a major cardiac anomaly and are more likely to have other major congenital anomalies. Since 2000, many countries in Europe have introduced national antenatal screening programs for Down syndrome. This study aimed to determine if the introduction of these screening programs and the subsequent termination of prenatally detected pregnancies were associated with any decline in the prevalence of additional anomalies in babies born with Down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
4
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 23 publications
9
67
4
4
Order By: Relevance
“…As previously reported, we found that infant girls were more commonly affected than infant boys. 27,28 Similar to findings in the general population, maternal obesity and maternal smoking were associated with increased risk of congenital heart defects within our cohort of infants with Down syndrome. 36,37 Our findings are strengthened by the population-based cohort study design and the use of prospectively recorded data from nationwide health care registers.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…As previously reported, we found that infant girls were more commonly affected than infant boys. 27,28 Similar to findings in the general population, maternal obesity and maternal smoking were associated with increased risk of congenital heart defects within our cohort of infants with Down syndrome. 36,37 Our findings are strengthened by the population-based cohort study design and the use of prospectively recorded data from nationwide health care registers.…”
supporting
confidence: 85%
“…27 However, the European Surveillance of Congenital Anomalies Central Register, including populationbased data from European countries including Sweden, recently reported an AVSD rate of 32%. 28 We can only speculate about underlying mechanisms for the shift in cardiovascular phenotype observed in Sweden, as we had no information on fetuses from terminated pregnancies. 29 In recent years, congenital heart defects are reportedly less common in the general population, but the magnitude of changes observed among Swedish infants with Down syndrome is unlikely to be explained by factors related to such small general trends.…”
Section: Discussionmentioning
confidence: 99%
“…From this latter group, only four fulfilled the eligibility criteria and were included in the meta-analysis [22][23][24][25]. Direct contact with the authors of the remaining 31 articles made it possible to include another eight studies [12,13,20,[26][27][28][29][30], totalizing 12 articles for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…One exception to the literature, AV canal (13.9%), is lower in our population than the previously identified 25-37%. Thirty-one percent of our population required surgical intervention for cardiac abnormalities, which is one of the few accounts reported in the literature but often a frequent question from parents [12][13][14]23].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…These investigations are significant in establishing a baseline to better understand this population. However, there are some limitations that include small participant numbers, data collection spanning many years, disparities in subject age range, lack of ethnic or race information and limited reliability of data systems for clinical information [7][8][9][10][11][12][13][14][15]. These challenges in the literature impact the reported frequency of comorbidities and limit our understanding of screening and identification of medical conditions for children with DS.…”
Section: Introductionmentioning
confidence: 99%